(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
An experimental and image analysis procedure were used to study the intra-ply shear behavior of 3- dimensional weft knitted spacer fabrics. In this work, the picture frame fixture was designed to determine its suitability for measuring intra-ply shear behavior of 3D spacer fabric. The nonlinear behavior of shear force versus shear angle and the deformation mechanism were analyzed. The shear force versus shear angle curves and wrinkles position of in-plane shear test are recorded by considering two different frame lengths to compare with each other and load-displacement curves of inter-ply shear test are also analyzed. In addition to this, the program was developed in matlab using Hough transform to analyze the shear angle in the image taken during displacement of specimen at various positions. This image analyzed results were compared with the actual experimental results. The findings of intra-ply shear behavior spacer fabrics using image processing and experimental techniques are important for various functional application. From the results obtained in this work, it is suggested that the picture frame fixture still requires minor modifications to increase the accuracy of shear behavior of textile materials.